Aggression: destructive impulse or life force - Fréchette, Louise (Bioenergetic Analysis, 2025)
The first part of this article retraces the evolution of the concept of aggression from the Freudian understanding of that primary impulse to the contemporary analytical authors, as well as to the Reichian and the Lowenian view of it. In a second part, it presents how today’s bioenergetic therapists conceptualize the aggressive impulse and how they work with it in their clinical practice, so that they can help their patients transform what can be a destructive force into a life force sustaining self-expression and self-actualization.